User Satisfaction with Resources and Services of Kumasi Technical University Library During the COVID-19 Pandemic - Boakye, Serwaa Akoto; Boakye, Ernest; Osei Kuffour Adjei, Kwabena (Ghana Library Journal, 2022)
A resourceful and well-organized library is an asset to any academic institution and its existence is justified by the extent to which users are satisfied with its resources and services. Nonetheless, globally, library services were affected by the outbreak of the COVID-19 pandemic. This study was therefore focused on determining the level of users’ satisfaction with the resources and services of Kumasi Technical University library during the COVID-19 pandemic. The survey method was employed and a questionnaire was used to collect data. Stratified and convenience sampling techniques were used to select 192 respondents but 169 responses were valid for analysis. The findings revealed that, generally, users were satisfied with the physical facilities, services and COVID-19 protocols in the library, though, the library provided poor online services, did not have discussion rooms, some users were not aware of electronic resources and few users did not follow COVID-19 protocols in the library. The study recommends the provision of discussion rooms, improvement in online services, publicity and training on electronic resources and provision of adequate water for handwashing and hand sanitizer.